Homophobic bullying in Mexican secondary level: Nuevo Leon context - Rodríguez Otero, Luis M. (2018)
Sexual orientation can become an element that favors the existence of bullying among students in the school environment. As there is no research in Nuevo Leon on homophobic bullying, this study aims to identify its existence and characteristics in the high schools of Monterrey, México. Through a mixed methodology and intentional sampling, 330 students were surveyed using an instrument with both open and close-ended questions. The results reveal that 44.54% of participants have witnessed bullying in their school (31.29% related to sexual orientation). In addition, we identified seven victims of homophobic bullying. It is necessary to propose legal, socioecological and preventive educational measures.